First-principles calculation of the effect of Ti content on the structure and properties of TiVNbMo refractory high-entropy alloy. (16th October 2020) - Chen, Lin; Hao, Xuanhong; Wang, Yueyi; Zhang, Xiaowei; Liu, Hongxi
Abstract: The virtual crystal approximation (VCA) method based on the Cambridge Sequential Total Energy Package (CASTEP) was used to establish the TiVNbMo refractory high-entropy alloy structure model. The effects of different Ti contents on the elastic and thermodynamic properties of Tix VNbMo (x = 1.00, 1.25, 1.50, 2.00) high entropy alloys were calculated. The lattice constants calculation results of TiVNbMo with equal atomic ratio match well with the experimental values of vacuum arc melting, indicating that the VCA method is suitable for the first-principles calculation of Tix VNbMo random solid solution. The EOS equation of state is used to determine the energy and volume of the equilibrium structure of the alloy. The elastic constants of Tix VNbMo (x = 1.00, 1.25, 1.50, 2.00) high entropy alloys are calculated based on the body-centered cubic structure, and their Young's modulus anisotropic three-dimensional contour stereograms are drawn. Moreover, the quasi-harmonic Debyeg-Grüneisen model is used to calculate the thermodynamic properties, such as thermal capacity, isothermal body modulus, volumetric thermal expansion coefficient, and Grüneisen parameter with Ti content and temperature.